The impact of Black South African English speaker’s accent on the quality of interpretation - Lebogo, Constantin Désiré (University of the Witwatersrand, Johannesburg, 2023)
As one of the three cognitive activities of interpreting, listening comprehension is key for ensuring quality in interpretation (Kamel, 2015). Listening comprehension requires a deliberate effort of hearing and comprehending the produced utterance by a speaker (Gile, 1995), and can, therefore, be affected by several variables, including the speaker’s accent. Besides other difficulties involved in interpreting, this study focuses on challenges related to listening to and understanding an accented Black South African English (BSAE) speech. It is assumed that a heavily accented speech by a Black South African English speaker will pose a challenge to an interpreter with no or little exposure to the specific variation of BSAE which, consequently, might impact performance and quality. This study seeks to investigate if an accented BSAE, might affect the quality of interpretation, and if so, to what extent. The questions raised here are addressed by comparing the level of accuracy and completeness of interpretation provided by two groups of professional interpreters with French (first language) and English (second language) as their language combinations. Interpretations into French by 13 participants of a video recorded speech, and the transcription of the same, read with a Standard British English accent were recorded. Thereafter, participants’ outputs were evaluated. This data including a questionnaire, was analysed using the mixed methods approach to test the hypothesis. The results suggest that the strong BSAE accent influenced the rendition of the message, as participants of the experimental group did not perform as well as those of the control group. The questionnaire elicited that accent and related factors, such as phonemics and prosody, represented the greatest challenge during the interpreting process. The study finally presents the strategies proposed and used by participants to mitigate accent impact on the process of interpreting and the quality of the output.
A Research Report submitted in partial fulfilment of the requirements for the award of Master of Arts in Translation by Course Work and Research Report (option: Interpreting), to the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, 2023.
Keywords: Accent; Black South African English (BSAE); Quality of interpretation; English; French; UCTD; SDG-4: Quality education